Kepatuhan Penggunaan Obat pada Pasien Geriatri dengan Polifarmasi - Retno Wulan D; Rusdiana Tri; Jihan Fahiroh; Elvira Silvany; Yasmine Eka; Vira Maulidya; Helmalia Jelita; Marscha Dwi; Mulia Maharani; Bella Fevi (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Polypharmacy in geriatric patients is the concurrent use of multiple medications that commonly occurs due to chronic diseases and multimorbidity. This condition can increase the risk of drug related problems (DRPs), adverse drug reactions, and decreased medication adherence among elderly patients. This study aimed to determine the relationship between polypharmacy and medication adherence in geriatric patients and to identify efforts that can improve adherence to therapy. The research method used was a literature review by searching articles through Google Scholar, PubMed, and ScienceDirect databases using the keywords “polypharmacy,” “medication adherence,” and “geriatric.” A total of 11 national and international journals published between 2016–2026 were selected according to the inclusion criteria. The review results showed that polypharmacy is associated with low medication adherence in geriatric patients due to therapy complexity, the large number of medications used, and cognitive limitations in elderly patients. Poor medication adherence may increase the risk of drug interactions, hospitalization, and therapeutic failure. Several interventions were found to be effective in improving adherence, including education and counseling by pharmacists, family support, therapy simplification through deprescribing, and the use of medication reminder applications. Therefore, the role of healthcare professionals and family support is essential in improving medication adherence and therapeutic outcomes in geriatric patients with polypharmacy.